The Efficacy of the proprioceptive neuromuscular facilitation (PNF) approach in stroke rehabilitation to improve basic activities of daily living and quality of life: a systematic review and meta-analysis protocol - Mercè Sitjà-Rabert; Francesc Xavier Guiu-Tula; Rosa Cabanas-Valdés; Gerard Urrútia; Natàlia Gómara-Toldrà (BMJ Open)
Introduction Proprioceptive neuromuscular facilitation (PNF) is a widely used rehabilitation concept, although its efficacy has not yet been demonstrated in stroke survivors. The aim of this systematic review is to identify, assess and synthesise the potential benefits of using PNF to improve the activities of daily living (ADL) and quality of life (QoL) of individuals with stroke.Methods and analysis A systematic electronic search will be conducted in MEDLINE, Embase, CENTRAL and PEDro. We will include randomised or quasi-randomised controlled trials of PNF interventions conducted in stroke survivors up to April 2017. Two review authors will independently select relevant studies and will extract data using the Cochrane handbook for systematic reviews of interventions approach and the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P). The methodological quality will be assessed by using the PEDro scale. Finally, with the permitted numeric data, we will carry out a meta-analysis.Ethics and dissemination Ethical considerations will not be required. Results will be disseminated in a peer-review journal. This systematic review aims to examine the effects of PNF (neurophysiological approach) in order to clarify its efficacy in improving ADL and QoL in the rehabilitation process of stroke survivors.PROSPERO registration number CRD42016039135.